Advanced Glycation End Products in the Pathogenesis of Psoriasis - Papagrigoraki, Anastasia (Int J Mol Sci, 2017)
Advanced glycation end products (AGEs) are extremely oxidant and biologically reactive compounds, which form through oxidation of sugars, lipids and amino acids to create aldehydes that bind covalently to proteins. AGEs formation and accumulation in human tissues is a physiological process during ageing but it is enhanced in case of persistent hyperglycemia, hyperlipidemia and oxidative or carbonyl stress, which are common in patients with moderate to severe psoriasis. Exogenous AGEs may derive from foods, UV irradiation and cigarette smoking. AGEs elicit biological functions by activating membrane receptors expressed on epithelial and inflammatory cell surface. AGEs amplify inflammatory response by favoring the release of cytokines and chemokines, the production of reactive oxygen species and the activation of metalloproteases. AGEs levels are increased in the skin and blood of patients with severe psoriasis independently of associated metabolic disorders. Intensified glycation of proteins in psoriasis skin might have a role in fueling cutaneous inflammation. In addition, AGEs released from psoriatic skin may increase metabolic and cardiovascular risk in patients with severe disease.